Immunobiological Methods for Monitoring Latent Tuberculosis Infection in Children and Adolescents and Analysis of Tuberculosis Infection Reactivation - M. A. Vladimirskiy; M. B. Lapenkova; A. A. Elov; V. A. Aksenova; M. A. Plekhanova; S. V. Smerdin; P. N. Rutkevich (Туберкулез и болезни лёгких)
The objective: to develop a new method to detect early subclinical signs of LTBI progression to the active disease.Subjects and Methods. Children under 18 years of age were enrolled in the study, of them 8 children suﬀered from pulmonary tuberculosis (TB Group) and 91 had LTBI (LTBI Group). Detection of subclinical signs of tuberculosis infection activity in LTBI Group included testing the concentration of antigen-speciﬁc induction of IFN-γ at the level more than 14 pg/ml, IL-6 more than 8 pg/ml and positive values of threshold cycles (Ct) of mRNA samples based on the results of real-time PCR of genes: PDCD1, PDL2, BATF2 and GBP5.Results. The developed method for detection of subclinical signs of tuberculosis infection activity in children and adolescents with LTBI consists of two components (immunological testing of concentration of IFN-γ and IL-6; and molecular genetic testing of mRNA expression of the PDL2, BATF2 and GBP5 genes). Simultaneous registration of IFN-γ and IL-6 levels and mRNA expression of the PDL2, BATF2 and GBP5 genes above reference values indicates a high risk of developing active tuberculosis. It was observed in 29/91 (31.9%) patients with LTBI, in whom chest CT revealed calciﬁcations in the upper lymph nodes or pulmonary lesions within 1 year.